Hazards in Full-disclosure Supply Chains - Ceravolo, Paolo; Cimato, Stelvio; Damiani, Ernesto; Frati, Fulvio; Gianini, Gabriela; Fugazza, Cristiano; Marrara, Stefiania; Scotti, Olga (Advanced Information Technologies for Management – AITM 2008, 2008)
Supply chain optimization is based on information shared with other partners or with a trusted external decision maker. Some works in the literature assume the full-disclosure paradigm, thinking that a peer increases the confidence in the alliance. In contrast to this claim, we underline that each participant to the coalition has its own objectives which need to be re-conciliated with the achievement of the common good. If achieving sueh common good reąuires completely missing their objectives, participants may be tempted to adopt a non-cooperative behavior. For this reason, supporting the representation and evaluation of information sharing risks is an important require- ment for implementing advanced supply chain management procedures. In particular in this work we discuss a methodology for analyzing information flow and identifying the data items that, if shared, can increase the risk of non-cooperative behavior. Also we demonstrate that, under given conditions, obfuscating this information can be a sufficient reąuirement for making cooperative behavior the best strategy to be adopted by participants.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 27-37